2022
DOI: 10.3389/fonc.2022.799982
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Lineage Switches in an Elderly Case of Refractory B-Cell Acute Lymphoblastic Leukemia With MLL Gene Amplification: A Case Report and Literature Review

Abstract: Lineage switches in acute leukemia occur rarely, and the underlying mechanisms are poorly understood. Herein, we report the case of an elderly patient with leukemia in which the leukemia started as B-cell acute lymphoblastic leukemia (B-ALL) and later changed to B- and T-cell mixed phenotype acute leukemia (MPAL) and acute myeloid leukemia (AML) during consecutive induction chemotherapy treatments. A 65-year-old woman was initially diagnosed with Philadelphia chromosome-negative B-ALL primarily expressing TdT/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…2 In our cohort, this phenomenon occurred in 7% of patients with KMT2Ar B-ALL treated in our institution. LS occurs primarily in KMT2Ar leukemias, usually in pediatric patients with ALL with t(4;11)/KMT2A::AFF1 rearrangement, [4][5][6] this last characteristic present in five of the six patients presented here. Patients with LS have poor prognosis, and current treatments do not have a high rate of success.…”
Section: Directed Therapiesmentioning
confidence: 62%
See 2 more Smart Citations
“…2 In our cohort, this phenomenon occurred in 7% of patients with KMT2Ar B-ALL treated in our institution. LS occurs primarily in KMT2Ar leukemias, usually in pediatric patients with ALL with t(4;11)/KMT2A::AFF1 rearrangement, [4][5][6] this last characteristic present in five of the six patients presented here. Patients with LS have poor prognosis, and current treatments do not have a high rate of success.…”
Section: Directed Therapiesmentioning
confidence: 62%
“…1,2 LS is rare, but its incidence may increase with the use of lymphoid lineage-targeting treatments, such as CD19-directed therapies. [3][4][5][6][7] Herein, we report one of the largest case series of patients with B-cell acute lympho-blastic leukemia (B-ALL) with KMT2Ar that had LS to a myeloid phenotype, all after receiving CD19-or CD22-directed therapy. The patients' baseline characteristics and the evolution of their diseases are detailed in Table 1 and Figure 1.…”
Section: Directed Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is more frequent when the initial neoplasm is of myeloid phenotype. Another hypothesis to explain the changes in the immunophenotype during relapse is clonal selection 15 . A previous study showed that MLL rearrangements were prevalent in almost 80% of pediatric patients with B-ALL who underwent lineage conversion to AML after chemotherapy with or without hematopoietic stem cell transplantation 11 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanisms are poorly understood. Moreover, the prognosis for these patients is variable, and there is no standard treatment 15 .…”
Section: Introductionmentioning
confidence: 99%